Fibrina Rica em Plaquetas associada à Bioestimulação a Laser no tratamento de recessões múltiplas: estudo clínico randomizado, duplo cego - Rodrigues, Célia Patrícia Müller (2024)
Gingival recession can cause functional and aesthetic problems, with surgical treatment often being indicated. The use of advanced platelet-rich fibrin (A-PRF) and low-level laser therapy (LLLT) have demonstrated considerable effectiveness. Objective: The objective of this study was to evaluate the effectiveness of using A-PRF associated with LLLT in root coverage in patients with multiple recessions. Study Designer: This study was designed with split-mouth groups, parallel randomized, double-blind. Place and duration of the study: The study was developed in the Dentistry clinics of the Universidade Estadual do Oeste do Paraná (UNIOESTE), in Cascavel-PR, Brazil, between March/2022 and July/2024. Methodology: 56 recessions were included, divided into Control Group: coronally positioned flap using A-PRF membranes and Laser Group: coronally positioned flap using A-PRF membranes associated with LLLT. The patients underwent periodontal root coverage surgery associated with A-PRF and a low-power laser was applied to one side of the arch postoperatively, in 5 sessions: immediately after surgery, 2, 4, 6 and 8 days after the surgical procedure. The patients were monitored for 0, 90 and 180 days, to verify periodontal clinical parameters, and the data were subsequently subjected to parametric and non-parametric statistical tests, with a significance level of 5% considered for all analyses. Results: In both groups there were improvements in root coverage and thickness of keratinized tissue in the evaluated periods (p<0.05), but without statistical difference when compared between groups (p>0.05). Conclusion: Both the use of A-PRF and A-PRF associated with LLLT brought satisfactory results for the coverage of multiple recessions, but without significant superiority between the two treatments.